A Bibliometric Study of the Factors Affecting the Rise in Gold Prices - Judijanto, Loso; Yuliawati, Refiana; Arini, Rani Eka (West Science Interdisciplinary Studies, 2025)
Gold has long been regarded as a safe-haven asset, particularly during periods of economic uncertainty, and its price is influenced by a complex interplay of macroeconomic, financial, and technological factors. This study employs a bibliometric analysis using Scopus as the primary data source and VOSviewer for network visualization to systematically examine the academic literature on the determinants of gold price fluctuations. The findings reveal three dominant research themes: macroeconomic influences (inflation, exchange rates, interest rates, and oil prices), gold’s role in financial markets and investment strategies, and emerging computational methods for gold price forecasting, particularly machine learning and artificial intelligence. The study highlights an increasing focus on gold’s relationship with cryptocurrencies and electronic trading, reflecting the evolving landscape of financial markets. Additionally, the co-authorship network analysis identifies key contributors and research clusters, indicating a growing interdisciplinary approach to gold price research. Despite the extensive body of literature, gaps remain in areas such as behavioral finance, sustainability, and digital finance innovations, presenting opportunities for future research. The findings of this study provide valuable insights for economists, policymakers, and investors, offering a comprehensive roadmap for understanding the evolving dynamics of gold prices.